2013
DOI: 10.1161/strokeaha.112.681254
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Institutional Caseload of Subarachnoid Hemorrhage on Mortality

Abstract: Background and Purpose-Procedures requiring specific skill sets often have been shown to depend on institutional volume, that is, centers receiving a higher volume observe better outcomes in those patients. This relationship recently has been shown to exist for subarachnoid hemorrhage(SAH) patients in a large study in the United States. We aim to examine this relationship for SAH patients in England, restricting analysis to specialist neurosurgical units. Methods-Aggregate counts of patients with SAH in 25 spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 34 publications
0
36
0
2
Order By: Relevance
“…Most previous studies of hospital volume and mortality after treatment for unruptured and ruptured intracranial aneurysms have found lower mortality in high-volume compared with low-volume hospitals, but different definitions of "low-volume hospital" make direct comparison with our study difficult. [1][2][3][4]7,8,13,14,[16][17][18] All previous studies except 1 have reported mortality at discharge. The lower mortality in high-volume hospitals may therefore have been confounded, for instance, by differences in length of stay and discharge routines.…”
Section: Discussionmentioning
confidence: 98%
“…Most previous studies of hospital volume and mortality after treatment for unruptured and ruptured intracranial aneurysms have found lower mortality in high-volume compared with low-volume hospitals, but different definitions of "low-volume hospital" make direct comparison with our study difficult. [1][2][3][4]7,8,13,14,[16][17][18] All previous studies except 1 have reported mortality at discharge. The lower mortality in high-volume hospitals may therefore have been confounded, for instance, by differences in length of stay and discharge routines.…”
Section: Discussionmentioning
confidence: 98%
“…We know that treatment in a high-volume hospital reduces morbidity and mortality. 7,8 An activity threshold of 20 cases per year used to be considered suitable, 9,10 but a more recent study showed that the impact of caseload on outcome persists well beyond this threshold. 8 In France, a neurointerventional center accepting patients with aneurysms for endovascular treatment is required to treat at least 80 patients per year.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 An activity threshold of 20 cases per year used to be considered suitable, 9,10 but a more recent study showed that the impact of caseload on outcome persists well beyond this threshold. 8 In France, a neurointerventional center accepting patients with aneurysms for endovascular treatment is required to treat at least 80 patients per year. Regionalization policies have been put in place worldwide during the past 20 years, based on the assumption, proven first in surgery, that highly experienced teams obtain better clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that clinical outcomes are more favorable at high-volume centers 6,12,15 ; a better strategy would be to transport the patient to a specialized center directly. Silbergleit et al 19 showed the cost-effectiveness of helicopter transportation of acute ischemic stroke patients.…”
Section: Outcomementioning
confidence: 99%